Gambaran Motivasi pada Pasien Kanker yang Menjalani Kemoterapi di Rumah Sakit Santa Elisabeth Medan Tahun 2024 - Usi Desi Christin Telaumbanua (Institut Nalanda, 2026)
Cancer is a non-communicable disease that is a public health problem, and is a chronic disease that requires long-term treatment and medication. Malignancy that occurs in body tissues where there are abnormal cells that grow excessively and uncoordinated. One of the treatments is chemotherapy therapy, a treatment given to stop the growth of cancer cells or slow the development of cancer cells in the body, where chemotherapy is a treatment method that uses very strong chemicals to stop or inhibit the growth of cancer cells in the body, chemotherapy also often creates motivation for patients who undergo it. Someone is motivated to recover, then he does daily activities within a certain time frame, there are high, sufficient, and low. Motivation is recognized as the driving force that drives someone to undergo chemotherapy. This study aims to determine the description of motivation in cancer patients undergoing chemotherapy at the Santa Elisabeth Hospital, Medan in 2024. This type of research uses a descriptive design with a sample size of 30 people. the results of the study are the motivation of cancer patients undergoing chemotherapy at Santa Elisabeth Hospital Medan as many as 29 respondents (96.7%) are included in the high motivation category. Researchers hope that for patients undergoing chemotherapy by ensuring that patients follow the chemotherapy schedule regularly and can increase the spirit of life and self- confidence of cancer patients with self-motivation and family support.